2016
DOI: 10.1177/0886260515624234
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment and Emotional and Behavioral Problems in Chinese Children With and Without Oppositional Defiant Disorder

Abstract: Maltreatment has negative effects on the parent-child relationship and the emotional and behavioral development of children. The current study aimed to examine the associations among maltreatment, parent-child relationship, and emotional and behavioral problems in Chinese children with or without oppositional defiant disorder (ODD). Participants in the study included 259 children with ODD and their 269 non-ODD counterparts from northern, eastern, and southwestern China. We also collected data from their teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 38 publications
(66 reference statements)
6
29
3
Order By: Relevance
“…As an entire level factor in the three‐level model of ODD (Lin et al, 2013), similar to the findings in previous studies (Li, Lin, Chi, et al, 2016; Lin, Li, Chi, et al, 2016; McKinney et al, 2018), in the current study, family violence was both directly and indirectly associated with ODD symptoms. In line with previous research findings, children exposed to maltreatment tend to exhibit more disruptive behaviours (Bingenheimer, 2005; Oshri, Sutton, Clay‐Warner, & Miller, 2015)—family violence is associated with more ODD symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As an entire level factor in the three‐level model of ODD (Lin et al, 2013), similar to the findings in previous studies (Li, Lin, Chi, et al, 2016; Lin, Li, Chi, et al, 2016; McKinney et al, 2018), in the current study, family violence was both directly and indirectly associated with ODD symptoms. In line with previous research findings, children exposed to maltreatment tend to exhibit more disruptive behaviours (Bingenheimer, 2005; Oshri, Sutton, Clay‐Warner, & Miller, 2015)—family violence is associated with more ODD symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…For parent–child relationship as a dyadic level factor, some evidence supports parent–child relationship was involved in the association of family violence with ODD symptoms by mediational processes (Li et al, 2016; Li, Lin, Hou, Fang, & Liu, 2016; McKinney, Stearns, & Szkody, 2018). Although the relations between parent–child relationship and ODD symptoms had been examined in previous studies (Li, Lin, Chi, et al, 2016; Li, Lin, Hou, et al, 2016; McKinney et al, 2018), it remains unclear how the specific dimensions of the parent–child relationship influence ODD symptoms. According to Armsden and Greenberg (1987), there are three dimensions in parental attachment: parental trust, parental communication and parental alienation.…”
Section: Introductionmentioning
confidence: 99%
“…There were differences between studies depending on whether it was the mother or the father of the child who was reporting on FF and parental MH problems (Burstein et al , ; Wang et al , ). Five of the studies which reported this association reported on differences in specific aspects of FF which did or did not mediate the relationship between ACEs and MH (Breaux et al , ; Burstein et al , ; Li et al , ; Platt et al , ; Wang et al , ). For example, Li and colleagues (2017) reported that among children with oppositional defiant disorder (ODD), the parent‐child relationship mediated the relationship between physical abuse and anger management, but not aggressive behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has some empirical support. Studies have shown that child maltreatment reduces children’s attachment to caregivers (Li et al, 2016; Mason, Russo, Chmelka, Herrenkohl, & Herrenkohl, 2017; Sousa et al, 2011) and that lower levels of attachment to parents are associated with higher levels of substance use in adolescence (Bahr, Hoffmann, & Yang, 2005; Hawkins et al, 1992; Kopak, Chen, Haas, & Gillmore, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%